Raman hyperspectral imaging detects novel and combinations of crystals in synovial fluids of patients with a swollen joint. (25th September 2022) - Niessink, Tom; Kuipers, Charline; de Jong, Brighton Z.; Lenferink, Aufried T. M.; Janssen, Matthijs; Jansen, Tim L.; Otto, Cees
Abstract: The identification of synovial crystals is important for diagnosing rheumatic diseases. Currently, rheumatologists worldwide use compensated polarized light microscopy (CPLM) for crystal identification, but this technique is flawed. Raman spectroscopy might offer an objective, accurate alternative. We have tested Raman hyperspectral imaging on synovial fluid samples of 28 patients with swollen joints, measuring 5–10 crystals in each of these. Reference spectra for identification were measured using patient material, synthetic compounds, and oxalate kidney stones. Additionally, RRUFF and PANGAEA Raman databases were used to identify spectra. We identified the classical pathological crystals monosodium urate for gout and calcium pyrophosphate for calcium pyrophosphate deposition disease (CPPD). Hydroxyapatite, lipid spherules, and calcium oxalate monohydrate have also been observed and had been previously identified in synovial fluids. Other crystals, which were not previously observed in synovial fluid using CPLM, have been identified as well: calcite, aragonite, anatase, rutile, thenardite, dolomite, and a carotenoid. In addition, we found combinations of crystals in 13 out of 28 patients. We propose that the observed large variation of detectable crystals from a small population of patients and a small number of crystals per patient has significant ramifications for the use of compensated polarized light microscopy for the diagnosis of gout and CPPD. Further studies are required to learn the clinical significance of these crystals in human arthritis. Abstract : Measured Raman spectra of crystals which were found in synovial fluids of patients with suspected gout or calcium pyrophosphate deposition disease.